1980
DOI: 10.3109/14017438009101016
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone in the Treatment of Lung Contusion Following Blunt Chest Trauma

Abstract: The effects of large doses of methylprednisolone (MP) (30 mg per kg. b.w.) in patients with lung contusion following blunt chest trauma were studied in 10 patients selected at random and compared with 10 chest trauma patients receiving no steroids, but otherwise treated in the same way. All patients survived. Serious post-traumatic complications were reduced in the steroid group. All patients were followed with haemodynamic and metabolic observations for 6 weeks using Swan-Ganz flow directed thermodilution cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…Our study is not in agreement with the retrospective study conducted by Svennevig et al [15], which showed significantly (p=0.02) lesser mortality of patients who were steroid treated (n=44) than compared to patients not treated with steroids (n=99) wherein study sample size was 143, with 72% patients multi-traumatized and 19% in shock. Furthermore, in steroid treated group, there was lower incidence of septicemia, bronchial infection, and multi-organ failure.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study is not in agreement with the retrospective study conducted by Svennevig et al [15], which showed significantly (p=0.02) lesser mortality of patients who were steroid treated (n=44) than compared to patients not treated with steroids (n=99) wherein study sample size was 143, with 72% patients multi-traumatized and 19% in shock. Furthermore, in steroid treated group, there was lower incidence of septicemia, bronchial infection, and multi-organ failure.…”
Section: Discussioncontrasting
confidence: 99%
“…The use of steroids may, in fact, contribute to decreased bacterial clearance [94] and subsequent increases in the risk of pneumonia. It has been suggested that steroids decrease pulmonary vascular resistance after injury, but the clinical benefit of this effect has not been established [113, 114]. Currently, corticosteroids have no role in the management of pulmonary contusion.…”
Section: Managementmentioning
confidence: 99%
“…Svennevig's study in 1980 compared 20 patients with pulmonary contusion, all of whom received standard treatment with randomization into steroid and non-steroid groups. No patient died in either group but there appeared to be a shorter period of hospitalization, requirement for ventilation and less infective complications in the steroid-treated group (Svennevig et al, 1980). Evidence from large numbers of patients with this condition has yet to be reported, although Lucas in 1984 could find no pulmonary benefit from the use of steroids in patients who had sustained blunt injuries to chest and other body regions (Lucas & Ledgerwood, 1984).…”
mentioning
confidence: 98%
“…They have been shown to inhibit complement-induced leucocyte aggregation (Hammerschmidt et al, 1979), and to block the increase in microvascular permeability following a variety of insults in experimental animals and humans (Brigham et al, 1981;Sibbald et al, 1981), probably as the result of inhibiting super-oxide radical release (Bihan & Tinker, 1982). Stabilization of cell and lysosomal membranes also occurs and some reports show improved pulmonary circulatory flow related to a fall in pulmonary venous resistance (Lucas & Ledgerwood, 1981;Svennevig et al, 1980;Dietzman & Lillehei, 1968). There follows an examination of some common clinical situations for which the use of steroids remains in contention.…”
mentioning
confidence: 99%